The European Union action in the field of rare diseases (Italian Journal of Public Health, 2009)
Background: Rare diseases, including those of genetic origin, are defined by the European Union as life-threatening or chronically debilitating diseases which are of such low prevalence (less than 5 per 10 000). Thespecificities of rare diseases - limited number of patients and scarcity of relevant knowledge and expertise -single them out as a unique domain of very high European added-value.Methods: The legal instruments at the disposal of the European Union, in terms of the Article 152 of theTreaties, are very limited. However a combination of instruments using the research and the pharmaceuticallegal basis and an intensive and creative use of funding from the Second Health Programme has permitted tocreate a solid basis that Member States have considered enough to put rare diseases in a privileged positionin the health agenda.Results: The adoption of the Commission Communication, in November 2008, and of the CouncilRecommendation, in June 2009, and the future adoption of the Directive on Cross-border healthcare, end2009 or mid 2010, have created an operational framework to act in the field of rare disease with Europeancoordination in several areas (classification and codification, European Reference Networks, orphan drugs,European Committee of Experts, etc.).Conclusions: Rare diseases is an area with enormous and practical potentialities for European cooperation.
Keywords: rare diseases; Europe